2022
DOI: 10.1002/cben.202100045
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Catalysis in Mixed Micelles

Abstract: The catalytic performance of lipase, an interfacially active enzyme, depends on the reaction medium. Novel reaction media like mixed micelles affect lipase catalysis mostly by stabilizing the lipase structure and increasing the substrate solubilization. Nonionic surfactant addition in ionic micelles formed mixed micelles and increased lipase catalysis by lowering detrimental lipase‐ionic surfactant hydrophobic and electrostatic interactions. Nonionic/nonionic mixed micelles enhanced activity and enantiomeric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…As a rule of thumb, non-ionic and zwitterionic surfactants have hydrophobic interactions with lipases, whereas the interactions of anionic and cationic surfactants with lipases are mainly electrostatic [77]. Likewise, surfactants may cause micelle formation at a given concentration, promoting a suitable microenvironment for the hydrolysis of hydrophobic substrates in aqueous solutions such as triglycerides [78]. In the case of SeLipC, sodium deoxycholate would stabilize the pNPP emulsion and create the appropriate micellar environment for enzyme catalysis as described for pancreatic lipase [79].…”
Section: Discussionmentioning
confidence: 99%
“…As a rule of thumb, non-ionic and zwitterionic surfactants have hydrophobic interactions with lipases, whereas the interactions of anionic and cationic surfactants with lipases are mainly electrostatic [77]. Likewise, surfactants may cause micelle formation at a given concentration, promoting a suitable microenvironment for the hydrolysis of hydrophobic substrates in aqueous solutions such as triglycerides [78]. In the case of SeLipC, sodium deoxycholate would stabilize the pNPP emulsion and create the appropriate micellar environment for enzyme catalysis as described for pancreatic lipase [79].…”
Section: Discussionmentioning
confidence: 99%
“…In the liquid–liquid separation process of forward extraction, lipase is transported from an aqueous medium to an organic phase where the enzyme is encapsulated in reversed micelles and protected from denaturation upon contact with the organic solvent, while in reverse extraction, the lipase does not remain in the reverse micelles for a long time but is simply transported into an aqueous media without any contaminant. Recently, surfactants are routinely used in RMS because they enhance the solubility of organic compounds and reduce surface tension [ 89 , 90 ]. In the context of industrial enzyme uses, the question of whether and how lipases and surfactants interact frequently arises.…”
Section: Purification Strategies Of Microbial Lipasesmentioning
confidence: 99%
“…In RMS, surfactants expand the interfacial area of the solvent which augments micelle formation and enzyme recovery from the system. This role of the surfactants and the formation of the micelle pave the way for robust downstream processing and a higher degree of enzyme purification [ 90 ]. Gaikaiwari et al [ 89 ] applied both the classical approach and reverse micellar approach for the purification of lipase from Pseudomonas and concluded that the RMS approach resulted in a 15-fold higher purification with 80% recovery in 45 min.…”
Section: Purification Strategies Of Microbial Lipasesmentioning
confidence: 99%
See 1 more Smart Citation
“…After entering the human body, TG is hydrolyzed into 2-monoglyceride (2-MG) and free fatty acids by pancreatic lipases [25] . Subsequently, 2-MG passes through the unstirred water layer (UWL) into the small intestinal epithelial cells as mixed micelles [26] . 2-MG was re-esterified with exogenous or endogenous long-chain fatty acids and reassembled with phospholipids, cholesterol and apolipoproteins to form lipoproteins (LPs) [27] .…”
Section: Introductionmentioning
confidence: 99%